2020
DOI: 10.3390/ma13132908
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu- and Zn-Doped Bioactive Glasses on the In Vitro Bioactivity, Mechanical and Degradation Behavior of Biodegradable PDLLA Scaffolds

Abstract: Biodegradable polymer scaffolds filled with bioactive glass particles doped with therapeutic metal ions are a novel and promising strategy to repair critical-sized bone defects. In this study, scaffolds based on a poly (D, L-lactide acid) (PDLLA) matrix filled with un-doped and Cu-, Zn- and CuZn-doped bioactive glass particles were produced by freeze-drying and a salt-leaching method. The effects of the doping and content of the glass particles (10 and 30 wt.%) on the morphology, compression properties, apatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…The pH of the solution increased during the incubation time, especially within the first day of soaking. The increase in pH values is related to the partial dissolution of the glass during the stages of the bioactivity process associated with the formation of a HAp layer on the surface of the 3D printed scaffolds, which in line with previous studies [46][47][48].…”
Section: Ph Measurementssupporting
confidence: 89%
“…The pH of the solution increased during the incubation time, especially within the first day of soaking. The increase in pH values is related to the partial dissolution of the glass during the stages of the bioactivity process associated with the formation of a HAp layer on the surface of the 3D printed scaffolds, which in line with previous studies [46][47][48].…”
Section: Ph Measurementssupporting
confidence: 89%
“…The ability to maintain the porous structure and mechanical properties during the generation of the cellular matrix and mineralization process is desirable. In this way, degradation studies in phosphate buffer solution (PBS) showed that the scaffolds lost almost 10% of their initial weights after 120 days of immersion [17]. In vitro tests performed in a previous study [21] showed cytocompatibility of the scaffolds against bone marrow stromal cells (ST-2), and its good angiogenic and osteogenic properties.…”
Section: Polymer Scaffolds Production 21 Salt Leachingmentioning
confidence: 89%
“…The pore diameter can be controlled by the size of the salt crystals, allowing pore interconnection and resulting in a very reproducible technique. However, this method has some disadvantages; for example, some degradation may occur when the material is exposed to water, and it is difficult to guarantee the complete removal of salt from samples [5,17]. Another shortcoming of this method is that it only allows the production of samples up to 3 mm thick [18]; besides that, sizes, dimensions, and shapes are limited by the mold in which the system polymer salt was poured.…”
Section: Polymer Scaffolds Production 21 Salt Leachingmentioning
confidence: 99%
See 2 more Smart Citations